The role of the school environment in increasing the academic achievement of basic stage students in Mafraq city schools from the point of view of its teachers - Salameh, Muhammad Asbeeh (Journal of Educational and Psychological Sciences, 2021)
This study aimed to identify the role of the school environment in increasing the academic achievement of the students of the basic stage in the schools of Mafraq city from the point of view of its teachers. To verify its validity and reliability, it was distributed among the available (30) of the study population, and it was processed statistically using the Statistical Package (SPSS) program, where the study concluded that there is a significant role for the school environment in increasing the academic achievement of the students. Students of the basic stage in Mafraq city schools from the point of view of their teachers, and it was found that there are statistically significant differences at the significance level (α ≤ 0.05) in the average responses of the study sample members towards the role of the school environment in increasing the academic achievement of stage students. The primary school in Mafraq city schools according to the study variable (gender, years of experience, educational qualification, specialization), and based on the results of this study, the researcher recommended several recommendations, the most important of which was that primary school teachers in Mafraq schools should rely on the encouragement method instead. About punishment, and it’s on teachers b Their plans denied that the student is the focus of the educational process and not following the old curriculum system.